The Use of Qur'anic Verses in the Indonesian Horror Film Munkar (2024): A Narrative Analysis Using Propp and Pierce's Semiotics - Alfi Faiqotul Bariroh Huda; Mukhlisin Saad; Muhibbin Muhibbin; Muh Amiruddin (KURAS Institute, 2025)
This study aims to provide an academic critique of the phenomenon of religious horror cinema in Indonesia by analyzing the film Munkar (2024). The research addresses the theoretical issue of commodifying sacred texts within the cinematic realm. Drawing on Vladimir Propp's narrative analysis and Charles Sanders Peirce's semiotics, the study examines how verses from the Qur'an are transformed from theological authorities into elements that evoke horror. The narrative analysis identifies 24 Proppian functions that position sacred verses as magical agents driving the plot. From a semiotic perspective, symbolic deconstruction emerges through the icon of the red mukena and the subversion of the mosque's sacred space, leading to the portrayal of a religious devil. The study's contribution confirms a pattern of desacralization of Islamic symbols, blurring the line between the sacredness of the text and the interests of the entertainment industry. These findings offer a new perspective on how popular media reconfigures discourses of morality and destiny through provocative horror imagery. Propp’s analysis reveals 24 narrative functions within the film’s plot, while Peirce’s semiotics examines icons, symbols, and indices related to these verses—such as Herlina’s red clothing, the mosque as a site of terror, prostration facing away from the qibla, and the roles of water, prayer beads, and the Qur’an in confronting evil forces. The results show that the film does not merely use Qur’anic verses as decorative or proselytizing elements, but also as tools to reinterpret Islamic values, depict the arrogance of the devil, illustrate the consequences of rejecting destiny, and convey the law of cause and effect (retribution) for unjust actions. However, there is also potential for a shift in meaning or commodification